GENERATION OF INFORMATION FOR MANAGEMENT DECISIONS BASED ON COST BEHAVIOUR ANALYSIS - G. A. Adamova (Вестник университета)
The article carries out a critical analysis of management information needs for information generation for operational and strategic management decisions. The problem of correct assessment of existing and future costs to substantiate the feasibility of the decisions is disclosed. The stages of formation of information on the value of variable and fixed costs associated with making managerial decisions are highlighted. The expediency of dividing fixed costs, depending on the duration of the period of validity of the decision, with which their occurrence is connected, has been substantiated. Recommendations for estimating costs in relation to specific products are given. Special attention is paid to the classification of costs into irreparable and avoidable costs, as well as to the division of the latter into risk categories based on the possible consequences of reducing or  completely eliminating various costs. Time, the study analyzes the difficulties  that arise in predicting future costs.